Mercury Inputs Into Eastern China Seas Revealed by Mercury Isotope Variations in Sediment Cores. Issue 8 (3rd August 2021) - Meng, Mei; Liu, Hongwei; Yu, Ben; Yin, Yongguang; Hu, Ligang; Li, Yanbin; Chen, Jiubin; Shi, Jianbo; Jiang, Guibin
Abstract: The mercury (Hg) loadings to the coastal regions of China have significantly increased in the last decades, and it is thus critical to unravel the input pathway and historical influx of these Hg. Here, concentrations and isotope compositions of Hg in three sediment cores collected from different mud areas of eastern China seas were comprehensively analyzed to investigate the spatial and temporal Hg inputs. The sediment core from nearshore mud area had distinctly higher δ 202 Hg and lower Δ 199 Hg values than those from offshore mud area, exhibiting an obvious difference in dominant Hg sources (land‐based vs. atmospheric). An isotope mixing model on basis of Hg isotope signatures of these cores revealed that the contributions of Hg sources varied significantly not only among different sites but also among different periods. Rapid development of industrialization and urbanization since the 1980s have significantly increased Hg especially industrial Hg inputs into eastern China seas. Our study suggests that the central mud area of Yellow Sea could well record the historical influxes of different Hg sources especially atmospheric Hg, as well as historical Hg emission events like industrialization/urbanization and modern Chinese wars, which would contribute to reconstruct the chronology of Hg inputs into eastern China seas. Plain Language Summary: Our study provides a multi‐dimensional map on the input and migration of Hg in eastern China seas from both spatial and temporal scales through an isotope mixing model on basis of the similarities and differences of Hg isotope signatures between nearshore and offshore sediment cores. The results revealed 1) the Hg inputs from major events in the past 160 yr such as industrialization/urbanization and modern Chinese wars and 2) the temporal variations in influxes of different Hg sources. We also observed notable even‐isotope mass independent fractionation signatures in one core, highlighting the possibility of atmospheric Hg 0 incorporation into sediments. Abstract :